Postliver Transplant Allograft Reinfection with a Lamivudine-Resistant Strain of Hepatitis B Virus: Long Term Follow-up. (1st May 1998) - Yoshida, Eric M; Ma, Mang M; Davis, Jennifer E; Fischer, Karl P; Kneteman, Norman M; Erb, Siegfried R; Tyrrell, D Lorne; Bain, Vincent G
Abstract : Lamivudine is a nucleoside analogue with efficacy in the suppression of hepatitis B viral (HBV) replication. In a previously reported study, lamivudine was administered to patients with chronic, actively replicating HBV infection who subsequently underwent liver transplantation. Patients became serum HBV DNA-negative in response to lamivudine before transplantation, which was continued in the post-transplant period. Two of four patients surviving the immediate postoperative period developed allograft reinfection 240 and 409 days post-transplant. The strain of the reinfecting virus was analyzed, and a mutation in the YMDD region of the viral polymerase conferring resistance to lamivudine was discovered. The long term follow-up of these two patients is reported. The first patient developed ascites 16.5 months after allograft reinfection. A transjugular liver biopsy performed 18 months after the emergence of the lamivudine-resistant strain revealed cirrhosis and lobular hepatitis without rejection. The gradient between hepatic vein wedged and free pressures was 13 mmHg, consistent with portal hypertension. The second patient, 16 months after allograft reinfection with the lamivudine-resistant strain, is without clinical evidence of portal hypertension, although liver enzymes remain elevated. Both patients were given a trial of famciclovir, which did not significantly suppress HBV viremia. In conclusion, lamivudine-resistant HBV strains with the YMDD mutation may have an aggressive clinical course with rapid progression to cirrhosis. Famciclovir did not appear to be an effective rescue agent in these two patients.